The Effect of Authoritative School Climate on Students’ Academic Achievement - Ismail, Siti Syamimi; Zainol, Zuraidah (International Business Education Journal, 2017)
This study was conducted to determine the effectiveness of authoritative school climate, particularly the disciplinary structure and student support, on student academic achievement. The study adopted a quantitative approach and a sample survey method. 200 students were selected from two secondary schools in Zone 5 Kinta Utara, Ipoh using a systematic sampling method. Multiple linear regressions were used to test the proposed hypotheses. The results show that the student supports have a significant and positive effect on the student’s academic achievement, but not disciplinary structure. Accordingly, to boost student achievement, the school administrators should adopt authoritative school climate, specifically by embedding the student support culture among all school teachers and support staffs. Despite the results provide insights on the significance of the authoritative school climate to increase student achievement, this study is subjected to some limitations, which require improvement and replication in future studies.